Model Penguatan Kesehatan Mental Tenaga Kesehatan Berbasis Kepemimpinan Inklusif dan Komunikasi Terpadu - Nano Isdiyanto; Dasrun Hidayat; Mira Veranita (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
The mental health of health workers is a crucial aspect that affects the quality of service in hospitals. High work pressure, complexity of medical cases, and communication challenges between teams are the main risk factors for psychological disorders among health workers. This study aims to design an integrated leadership and communication development model as a strategic effort to support the mental health of health workers at Jannah Hospital Serang. The approach used in this research is a qualitative method with a descriptive study design. Data were collected through in-depth interviews, participatory observation, and documentation studies involving medical personnel, hospital leaders, and support staff. Analyses were conducted using thematic analysis techniques to identify patterns, needs, and barriers in aspects of leadership and internal hospital communication. The results showed that inclusive and empathic leadership, as well as open and structured communication, contributed significantly to improving the psychological well-being of health workers. Based on these findings, an integrated communication-based leadership development model was formulated that includes transformative leadership training, a two-way communication system, and HR engagement. This model is expected to be a reference in strengthening the hospital's human resource management system oriented towards mental health, as well as improving the work effectiveness and satisfaction of health workers in a sustainable manner